The Role of Evidence-Based Practice in German Special Education-State of Research and Discussion - Yvonne Blumenthal; Bodo Hartke; Stefan Voß (MDPI AG, 2019)
This paper reviews the discourse on the concept of evidence-based special education in Germany. A short overview of the current situation in regard to available evidence-based educational materials for schools in Germany and the USA is given. Critical objections on the topic within Germany will be outlined thereafter. With these in mind, a discussion on the described points of criticism will follow in closing. Overall, the concept’s essential elements, such as the social and internal evidence, are not given sufficient consideration.